2013
DOI: 10.1021/ic401052a
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization Reactions Characteristic of a Robust Bicyclic Diphosphane Framework

Abstract: The 3,4,8,9-tetramethyl-1,6-diphospha-bicyclo-[4.4.0]deca-3,8-diene (P2(C6H10)2) framework containing a P-P bond has allowed for an unprecedented selectivity toward functionalization of a single phosphorus lone pair with reference to acyclic diphosphane molecules. Functionalization at the second phosphorus atom was found to proceed at a significantly slower rate, thus opening the pathway for obtaining mixed functional groups for a pair of P-P bonded λ(5)-phosphorus atoms. Reactivity with the chalcogen-atom don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…Previous studies have shown excellent selectivity in functionalizing only one of the phosphorus atoms in 1 . 16 As expected, phosphino-phosphonium salt [Me-P 2 (dmb) 2 ]I ( 2 ) was obtained in 90% yield after treatment of 1 with methyl iodide in diethyl ether at room temperature overnight. The structure of [Me-P 2 (dmb) 2 ]I was confirmed by X-ray crystallography (Fig.…”
supporting
confidence: 69%
“…Previous studies have shown excellent selectivity in functionalizing only one of the phosphorus atoms in 1 . 16 As expected, phosphino-phosphonium salt [Me-P 2 (dmb) 2 ]I ( 2 ) was obtained in 90% yield after treatment of 1 with methyl iodide in diethyl ether at room temperature overnight. The structure of [Me-P 2 (dmb) 2 ]I was confirmed by X-ray crystallography (Fig.…”
supporting
confidence: 69%
“…In view of the very similar features of the molecular and 2D material processes and computationally proved their feasibility, we strongly hope that such a reactivity will be addressed in laboratory, also being supported by precedent experimental investigations on diphosphane. 13 The results of the present manuscript will represent the starting point for a more efficient functionalization.…”
Section: Discussionmentioning
confidence: 82%
“…Sulphur transfer reactions between trisubstituted pnictogens (R 3 E) have been successfully addressed with phosphorus and arsenic with a large variety of organic groups. 12 More recently, Cummins et al 13 reported an efficient method for bringing about the selective sulfuration of a cyclic diphosphane using triphenylstibine sulfide as the S-transfer reagent. Remarkably, the stepwise formation of the P(E) bond (E = O or S) was achieved without affecting the original P-P bond.…”
Section: Introductionmentioning
confidence: 99%
“…[53] The products formed after consecutive [4+ +2]-cycloadditions to afford unique organodiphosphanes 49,w hich have been shownt oc oordinate to Group 10 metals [54] and undergo chalcogenation and alkylation reactions to allow furtherf unctionalization of the bicyclic structures. [55,56] Whereas this photochemical protocol transfersc leanly Pa toms from P 4 into organic frameworks, the isolated yields are only moderate (R = H, 2%;R= Me, 34 %) due to their lability under the harshirradiation conditions. The transfer of aP 2 fragment to an organic substrate was also achieved by Mathey and co-workers, [57] who showed that upon mixing (trimethylsilyl)diazomethanide with P 4 ,aformal [3+ +2]-cycloaddition reactiono ccurs to form diazadiphospholide anion 50 and neutral 51 after protonation (Scheme 21).…”
Section: Functionalization Of P 4 Through P 2 Fragmentsmentioning
confidence: 99%
“…In 2010, the group of Cummins reported on photochemically generated P 2 that was captured in situ by DA reactions with 1,3‐dienes (Scheme ) . The products formed after consecutive [4+2]‐cycloadditions to afford unique organodiphosphanes 49 , which have been shown to coordinate to Group 10 metals and undergo chalcogenation and alkylation reactions to allow further functionalization of the bicyclic structures . Whereas this photochemical protocol transfers cleanly P atoms from P 4 into organic frameworks, the isolated yields are only moderate (R=H, 2 %; R=Me, 34 %) due to their lability under the harsh irradiation conditions.…”
Section: Functionalization Of P4 Through P2 Fragmentsmentioning
confidence: 99%